Chemo brain or not, an intervention is necessary. - Espersen, Brigitte T; Brandborg, Anne M (Danish Journal of Nursing / Sygeplejersken, 2012)
Some patients complain about cognitive changes during and after chemotherapy. The patients mention memory problems forgetfulness, difficulties in learning new things and problems coping at work. However, an international study ahs found a divergence between the symptoms patients describe and the results of objective tests, which may contribut to the patients not having their problems acknowledged. It is not onclusively known what causes the patients' symptoms nor are there at the moment any evidence-based interventions that patients, their families or healthcare providers can use to alleviate the symptoms. The article presents arguments that healthcare providers should acknowledge the cognitive changes that the patients and their families report. A number of examples of advice and guidance are presented in the article concernng both specific symptoms and their emotional consequences.